A review of low-frequency latex harvesting systems that lessen the tapper shortage problem of the smallholders' natural rubber production - Zaw, Zar Ni (Kultivasi, 2023)
Smallholders' rubber production is encountering problems of skilled tapper shortage and high production costs resulting from increased worker wages and the substantial growth of new mature areas. Low-frequency latex harvesting system (LFLHS) effectively improves tapper productivity with long-term optimum yield by reducing the tapper requirement. LFLHS reduces tapper requirement by 33% to 67% of the conventional harvesting systems. Under the d3 (tapping every three days) frequency harvesting system, a tapper is assigned to cover three tasks, and his productivity is at least 30% higher than that of the d2 (alternative daily) frequency harvesting system. The cumulative yield of LFLHS is comparable to that of d2 frequency. It is economically profitable when the cumulative yield of LFLHS reaches 90% of the d2 frequency tapping as a break-even yield. Its low number of tapper requirement and high productivity saves tapping cost. 20% to 55% of tapping cost can be reduced by shifting the harvesting frequency from d2 to d3. The virgin bark of basal panels could be tapped at least four to ten years more than conventional tapping systems. The low bark consumption allows sufficient time for the regeneration of bark tissues resulting in a potentially higher yield from the renewed bark. Thus, sustainable economic yield is achievable for a productive lifespan of 30 to 35 years from the LFLHS. These advantages of LFLHS contribute to reducing the tapper requirement and cost of production, ensuring increased profits and a longer economic lifespan of rubber production.Keywords: Latex harvesting system, Tapper requirement, Tapper productivity, Tapping cost